2005
DOI: 10.1158/0008-5472.can-04-1941
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen Derivative 5α-Androstane-3β,17β-Diol Inhibits Prostate Cancer Cell Migration Through Activation of the Estrogen Receptor β Subtype

Abstract: Prostate cancer growth depends, in its earlier stages, on androgens and is usually pharmacologically modulated with androgen blockade. However, androgen-ablation therapy may generate androgen-independent prostate cancer, often characterized by an increased invasiveness. We have found that the 5A-reduced testosterone derivative, dihydrotestosterone (the most potent natural androgen) inhibits cell migration with an androgen receptor-independent mechanism. We have shown that the dihydrotestosterone metabolite 5A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
100
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 52 publications
7
100
0
4
Order By: Relevance
“…In pursuit of a functional basis for this relationship, we demonstrated that ERβ sustains an epithelial phenotype and impedes a mesenchymal transition in prostate cancer and we identified a metabolite of dihydrotestosterone, 5α-androstane-3β,17β4-diol (3β-adiol) as the specific ERβ ligand that mediates this function (9). This observation is in agreement with the recent findings that 3β-adiol is a natural ligand for ERβ in prostate (13,(15)(16)(17).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In pursuit of a functional basis for this relationship, we demonstrated that ERβ sustains an epithelial phenotype and impedes a mesenchymal transition in prostate cancer and we identified a metabolite of dihydrotestosterone, 5α-androstane-3β,17β4-diol (3β-adiol) as the specific ERβ ligand that mediates this function (9). This observation is in agreement with the recent findings that 3β-adiol is a natural ligand for ERβ in prostate (13,(15)(16)(17).…”
supporting
confidence: 93%
“…The ligand dependency of ERβ-mediated regulation of PHD2 expression was evaluated by treating both PNT1a and LNCaP cells with 3β-adiol, a natural ligand for ERβ in the prostate (9,13,(15)(16)(17). Indeed, 3β-adiol treatment caused a significant increase in PHD2 mRNA and protein expression in both cell types Author contributions: P.M., C.C., and A.M.M.…”
Section: Phd2 Expression Is Regulated By Ligand-dependent Activation mentioning
confidence: 99%
“…41 It has also been shown that ERb negatively affects malignant cell tumorigenesis. 19,42,43 Although to our knowledge the exact correlation between ERb expression and tumor progression in thymic epithelial tumors is still unclear, ERb is suggested as a potential target in the treatment of ERb-positive thymomas and thymic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that 3βAdiol can bind to both ERα and ERβ with approximately 30-fold and 14-fold lower affinity relative to that of E2, respectively, suggesting slight specificity for ERβ [13]. 3βAdiol has been extensively characterized as an ERβ ligand in in vitro ERβ-promoter driven luciferase assays [18,19], gene expression assays [20,21], and in vivo prostate and prostate cancer models [22,23]. 3βAdiol has been shown to play a well defined role in prostate cancer etiology as an ERβ ligand.…”
Section: Discussionmentioning
confidence: 99%